2014
DOI: 10.1186/2052-336x-12-62
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermodynamic studies for removal of acid blue 129 from aqueous solution by almond shell

Abstract: Efficiency and performance of Almond shell (AS) adsorbent for the removal and recovery of Acid Blue 129 (AB129) from wastewater is presented in this report. The influence of variables including pH, initial dye concentration, adsorbent dosage, particle size, contact time and temperature on the dye removal have been investigated in batch method by one at a time optimization method. The experimental equilibrium data were tested by four widely used isotherm models namely, Langmuir, Freundlich, Tempkin and Dubinin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…As seen in the figure, a period of 60 minutes was found to be sufficient for removal of Cu(II) with almond shell. Some of the previous researches similarly reported 60 minutes contact time for heavy metal removal with almond shell [15]; in other studies lower [16,17] and higher [14,18] contact times were also reported.…”
Section: Adsorption Experimentsmentioning
confidence: 82%
“…As seen in the figure, a period of 60 minutes was found to be sufficient for removal of Cu(II) with almond shell. Some of the previous researches similarly reported 60 minutes contact time for heavy metal removal with almond shell [15]; in other studies lower [16,17] and higher [14,18] contact times were also reported.…”
Section: Adsorption Experimentsmentioning
confidence: 82%
“…Also, it was found that the volume of effluent treated increased with increasing the bed depth This was attributed to an increase in the surface area and the number of binding sites available for adsorption. The time for interaction of adsorbate and adsorbent also increased with increasing amount of adsorbent (Fathi et al 2014;Teutscherova et al 2018) pH of adsorbate (pH) In some case, highest removals are found at acidic pH and maximum removals of some adsorbate are found at alkaline pH It depended upon the nature of adsorbent and adsorbate (Banerjee and Chattopadhyaya 2013;Ahmed and Hameed 2018) Particle size of adsorbent (PSA) Breakthrough and exhaustion times are slower with increasing particle size of adsorbent. Maximum particle size is favored to get better adsorption capacity.…”
Section: Adsorption Models For Column Studymentioning
confidence: 99%
“…The results of the Freundlich isotherm also indicate that biosorption at pH 8.50 is likely a physical process. Through the analysis of thermodynamic parameters, one can determine whether the biosorption process is spontaneous, exothermic, or endothermic (Fat'hi et al 2014). The positive entropy value (Table 3) demonstrates randomness during biosorption.…”
Section: Isotherm Studiesmentioning
confidence: 99%